Navigating Open Adoption: Insights from Adoptive Families in Spain - Berástegui Pedro-Viejo, Ana; Ramos, Nerea; Gómez Bengoechea, Blanca (My University, 2025)
.

This study explores pioneer parents’ perspectives on open adoptions in Spain, primarily involving contact with birth siblings. Five interviews with parents in open adoptions were analyzed using thematic analysis. Four content blocks emerged: motivation and decision-making, adaptation and family life, post-adoption contact, and general evaluation. Families accept open adoption as a necessary condition for adoption. Parents and children are well adapted, with no specific initial problems identified. Contact varies significantly from one case to another. The overall assessment of open adoption by pioneering families in Spain is positive, although its suitability should be evaluated on a case-by-case basis.
Artículos en revistas